Comparison of sociocultural attitudes towards epilepsy in Limousin (France), in Togo and in Benin (Africa) - Nubukpo, Philippe; Preux, Pierre-Marie; Clement, J. P.; Houinato, Dismand; Tuillas, M.; Aubreton, C. HUBERT; Radji, A.; Grunitzky, E. K.; AVODE, DOSSOU GILBERT; Tapie, P. (My University, 2003)
Sociocultural attitudes continue to have a negative impact on management of epilepsy in many African countries and in a few advanced countries. The purpose of this study was to compare attitudes toward epilepsy in France and two African nations: Togo and Benin. A total of 305 epileptic patients over 18 years of age were interviewed using the same quantitative questionnaire about their beliefs, knowledge attitudes and practices regarding their disease. There were 77 patients from the Limousin region in France, 129 from the rural canton of Nadoba in Togo and 99 from the coastal province in Benin. The frequency of epileptic seizure during the last two years prior to the study was lower in France than in Togo and Benin. The number of people who believed in supernatural causes of epilepsy was higher in Togo and Benin whereas the number of people attributing the disease to social causes (e.g. death and stress) was higher in France. Few epileptic patients in France thought that the disease was contagious whereas many patients in both Togo and Benin still believed that the disease was contagious and that some foods were forbidden. More patients in France than in Togo and Benin were aware of the relationship of epilepsy with alcohol, drug abuse and cerebral injury. Epileptic patients in France were more likely to consult a physician and use medical drugs for the treatment of epilepsy than their counterparts in Togo and Benin. Epileptic patients in Togo often complained of social exclusion. Although sometimes contradictory, these findings support the idea that sociocultural attitudes should be taken into account in the management of the disease.
Keywords: Comparison; sociocultural attitudes; epilepsy